Interaction parameters of oxygen and deoxidants in liquid iron - Costa e Silva A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
During decades before the evolution of more powerful computational tools, simplified formalisms such as the Wagner dilute solution formalism, have been successfully used in the study of deoxidation reactions of steel. This formalism relies on the introduction of interaction coefficients to account from deviations from Henry’s Law. With the evolution of thermodynamic modeling and of the CALPHAD method, the fact that thermodynamic descriptions using these parameters were derived to be used at relatively dilute solution has been sometimes overlooked and the formalism has been criticized for deviating from reality in non-dilute solutions. In this work, it is shown that the interaction parameters used in this formalism correlate with properties of the solutes and of the solvent. The work focuses on the interactions in systems Fe-M-O, where M is a deoxidant. Correlations between interaction coefficients and heats of formation of the corresponding oxides and with the atomic number of the deoxidants are demonstrated. This not only helps supporting the physicochemical soundness of the formalism but also provides a way of checking the consistency of data presented in this formalism.